2014
DOI: 10.1371/journal.pone.0113112
|View full text |Cite
|
Sign up to set email alerts
|

What Are Fair Study Benefits in International Health Research? Consulting Community Members in Kenya

Abstract: BackgroundPlanning study benefits and payments for participants in international health research in low- income settings can be a difficult and controversial process, with particular challenges in balancing risks of undue inducement and exploitation and understanding how researchers should take account of background inequities. At an international health research programme in Kenya, this study aimed to map local residents' informed and reasoned views on the effects of different levels of study benefits and pay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
66
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 25 publications
(35 reference statements)
1
66
0
Order By: Relevance
“…Given recognized concerns about balancing appropriate compensation against concerns about undue risk 2123 , the CHMI study team consulted widely within the research Programme regarding the levels and types of compensation to provide. The daily amount provided was in line with average earning for the local community to whom the study was relevant, as was reported in the interviews.…”
Section: Discussionmentioning
confidence: 99%
“…Given recognized concerns about balancing appropriate compensation against concerns about undue risk 2123 , the CHMI study team consulted widely within the research Programme regarding the levels and types of compensation to provide. The daily amount provided was in line with average earning for the local community to whom the study was relevant, as was reported in the interviews.…”
Section: Discussionmentioning
confidence: 99%
“…Far less has been documented, empirically, about practices, attitudes and policies related to provision of goods to research participants in lowand middle-income countries (LMICs), though concerns have been expressed (Boutin-Foster et al, 2013;Dickert & Grady, 1999;Hyder, Rattani, Krubiner, Bachan, & Tran, 2014;Molyneux et al, 2012;Njue et al, 2015;Njue, Kombe, Mwalukore, Molyneux, & Marsh, 2014). Few studies in sub-Saharan Africa have assessed the types of benefits offered to participants and fairness of such benefits (Molyneux et al, 2012;Njue et al, 2014). These studies focused on benefits offered in studies conducted by the Kenya Medical Research Institute (KEMRI)-Wellcome Trust program in Kilifi, Kenya.…”
Section: Introductionmentioning
confidence: 99%
“…This paper draws on a qualitative study set up as a community consultation on study benefits and payments to support the development of locally responsive policies at an international health research programme in Kilifi, Kenya, and to contribute to wider international debates. Findings on the ethical work of boundaries for levels of benefits and payments from this consultation have been published elsewhere [ 10 ]. An earlier study explored common practices and the views of diverse research staff on study benefits and payments at the programme [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…These livelihoods present challenges for identifying appropriate levels of compensation for time, with any underestimates potentially impacting on a bread winner’s ability to feed their family on a daily basis. Risks of ‘overcompensation’ were also seen, primarily in relation to the researcher-participant/community relationships, including commercialisation, loss of trust and generation of rumours; but also in terms of benefits introducing inequities and disrupting values within families and communities [ 10 ]. As noted above, this paper focuses on the role of the nature of benefits in influencing these and other ethical challenges.…”
Section: Introductionmentioning
confidence: 99%